Highly transparent, ultra‐thin flexible, full‐color mini‐LED display with indium–gallium–zinc oxide thin‐film transistor substrate. Issue 12 (5th November 2020) - Sun, Yang; Fan, Jack; Liu, Minggang; Zhang, Lijun; Jiang, Bei; Zhang, Min; Zhang, Xin
Abstract: Mini‐LED and micro‐LED are expected to be the next‐generation display by virtue of their diverse applications. In this study, an 8‐inch flexible mini‐LED display was fabricated using an indium–gallium–zinc oxide (IGZO) thin‐film transistor (TFT) backplane that adopted a top‐gate structure, with a pixel pitch of 0.55 mm and a resolution of 320 x 160, 46 PPI. With colorless polyimide (CPI) as the substrate, the mini‐LED panel has a thickness of less than 0.2 mm, and a transmittance is over 60%. The world's first 8‐inch, full‐color, flexible mini‐LED with IGZO‐TFT backplane is demonstrated. Abstract : We designed an 8‐inch flexible mini‐LED display based on an IGZO TFT backplane. The TFT backplane adopted top‐gate structure and designed with 0.55 mm pixel pitch and achieved a resolution of 320 × 160, 92 PPI. The novel flexible display demonstrated a high transparency, ultra‐thin, and high color gamut properties.